Occurrence of filamentous fungi in drinking water: their role on fungal-bacterial biofilm formation - Afonso, Tiago André Barros (2021)
Water is indispensable to life and safe and accessible supply must be available to all. The presence of microorganisms is a threat to this commitment. Biofilms are the main reservoir of microorganisms inside water distribution systems and they are extremely ecologically diverse. Filamentous fungi and bacteria can coexist inside these systems forming inter-kingdom biofilms. This review has the goal of summarizing the most relevant and recent reports on the occurrence of filamentous fungi in water distribution systems along with the current knowledge and gaps about filamentous fungal biofilm formation. Special focus is given on fungal-bacterial interactions in water biofilms.